2006
DOI: 10.1097/01.rli.0000188026.20172.5d
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Low-Contrast Detectability in Low-Dose Hepatic Multidetector Computed Tomography Using a Novel Adaptive Filter

Abstract: The radiation dose can be reduced by 50% without loss of nodule detectability by applying the adaptive noise reduction filter to simulated and patient liver images obtained at MDCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
0
28
1
1
Order By: Relevance
“…Low-pass (smoothing) algorithms reduce noise by filtering out higher frequencies; however, the filtering is indiscriminate and important object boundaries can be smoothed concomitantly [21]. Data presented here for the smoothing algorithm further support this low-pass limitation and emphasise that preservation of interfaces is required for the detection of low-contrast objects.…”
Section: Discussionmentioning
confidence: 71%
“…Low-pass (smoothing) algorithms reduce noise by filtering out higher frequencies; however, the filtering is indiscriminate and important object boundaries can be smoothed concomitantly [21]. Data presented here for the smoothing algorithm further support this low-pass limitation and emphasise that preservation of interfaces is required for the detection of low-contrast objects.…”
Section: Discussionmentioning
confidence: 71%
“…The largest dose decrease for the thoracic imaging was achieved for the CT of the pulmonary arteries (up to 42%). However, no reduction of the radiation dose was achieved after the education and training programme for abdominal CT. A possible explanation for this finding might be the radiologists' concerns about suboptimal image quality resulting from lower dose CT protocols, possibly leading to a greater risk of overlooking low contrast lesions [21][22][23][24]. Conversely, a marked reduction in the radiation dose is feasible in thoracic CT imaging because the increase in image noise is compensated for by the inherent contrast between air (lower attenuation) and the pulmonary vessels and interstitial structures (higher attenuation).…”
Section: Discussionmentioning
confidence: 99%
“…4 A technique using a noise reduction fi lter is useful for reducing the radiation dose at CT examination. [5][6][7][8] We previously reported the usefulness of our novel adaptive noise reduction fi lter during hepatic CT. 9,10 In that study, we used a computer-simulated liver phantom and a fi xed fi lter magnitude to achieve smoothness and sharpness because the size of the phantom was constant. We found that the radiation dose could be reduced by 50% without losing low-contrast detectability.…”
Section: Introductionmentioning
confidence: 99%
“…We also conducted a clinical study involving 15 patients to examine the characteristics of the constant fi lter. 10 For routine clinical practice, the effect of the fi lter may vary according to patient conditions such as body weight. Therefore, optimizing the adaptive noise-reduction fi lter according to the patient constitution (body weight) may be required.…”
Section: Introductionmentioning
confidence: 99%